HAMBATAN PENDAFTARAN INDIKASI GEOGRAFIS TAHU SUMEDANG SEBAGAI ASET POTENSIAL DAERAH - Yudha Agung Nugraha; Imam Haryanto (Keadilan : Jurnal Fakultas Hukum Universitas Tulang Bawang, 2020)
The purpose of this paper is to examine the barriers to registering geographic indications of Sumedang as potential regional assets. The research method used in the research is normative juridical research which means that it is carried out by examining library materials or secondary materials, then analyzing issues concerning Geographical Indications and their benefits to the area of ​​origin. The results of the analysis raise 2 themes discussed here, barriers to registering geographical indications of Sumedang tofu, as well as the impact on product listing as geographic indications. A study of these two themes is very useful in understanding the importance of registering geographic indications as well as the benefits generated by protecting Geographical Indications. Keywords : Geographical Indications, Sumedang, Benefits of Geographical Indications